2012
DOI: 10.1097/fch.0b013e3182465058
|View full text |Cite
|
Sign up to set email alerts
|

Salud Para Su Carozón—A Latino Promotora-Led Cardiovascular Health Education Program

Abstract: Salud Para Su Carozón is a culturally sensitive, community-based program to increase heart healthy knowledge and behaviors among Latinos. Promotoras were trained using a 10-session manual to teach participants from 7 communities about heart disease risk factors and skills to achieve heart healthy behaviors. In 435 participants with pre-to-post self-reported data, there were increases in physical activity outside of work (57%-78%), heart health knowledge (49%-76%), and confidence in preparing heart healthy meal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 12 publications
2
23
0
Order By: Relevance
“…20,21 This culturally-tailored intervention for Latinos, a NHLBI model curriculum, includes a variety of interactive teaching strategies. 22 Similarly positive outcomes are reported from a multi-site study involving culturally diverse, high-risk women attending a comprehensive heart care program within hospital clinics and healthcare centers.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 This culturally-tailored intervention for Latinos, a NHLBI model curriculum, includes a variety of interactive teaching strategies. 22 Similarly positive outcomes are reported from a multi-site study involving culturally diverse, high-risk women attending a comprehensive heart care program within hospital clinics and healthcare centers.…”
Section: Introductionmentioning
confidence: 99%
“…First, CHW interventions have positive health outcomes for the population served. Systematic reviews, empirical studies and meta-analyses demonstrate that CHW interventions can improve, and have contributed to, a range of health issues, such as screening among immigrants 28,29,36,37 and other marginalized populations, 37 diabetes and asthma management, 36,38,39 healthy heart lifestyle, 40 maternal and child health services, 41 healthy eating habits, blood pressure reduction, patient enrolment in research, child development, early intervention services, 35,42,43 health care utilization, and some disease prevention and public health concerns. 36,44 Second, evaluations of CHW interventions have indicated their potential to reduce health disparities in marginalized populations.…”
Section: Evaluation Studiesmentioning
confidence: 99%
“…17,21 Risk factors that were commonly mentioned in our study, as well as others, include poor diet, lack of exercise, worries and stress, overweight, hypertension, high cholesterol, and access to medical care. 13,15,17,18,22 Participants in others studies were not aware of other common risk factors, 13,17 suggesting the need of conveying basic CVD information. In fact, one qualitative study purposely recruited Puerto Rican women with at least a high school education and without previous heart disease, to avoid bias in knowledge, but that study also showed that participants did not have proper knowledge or did not feel confident about it.…”
Section: Discussionmentioning
confidence: 99%
“…We used focus group discussions for this formative research because these have been effectively used to evaluate and understand a community’s knowledge, opinions, and needs to design culturally-appropriate programs. 14,1517 …”
mentioning
confidence: 99%